Service Operations Efficiency in Public Ferry Transportation at Baubau Port: JEL Classification: H83, L91, R41, R48, Z32 - La Ode Irman Saputra (Generasi Sains Indonesia, 2026)
This study examines service operations efficiency in public ferry transportation at Baubau Port using a public management perspective. The research aims to analyze the influence of administrative efficiency, operational reliability, service responsiveness, institutional coordination, and service accessibility on transportation operational efficiency. A quantitative survey approach was conducted involving 200 ferry transportation users selected through purposive sampling. Data were analyzed using descriptive statistics and multiple linear regression analysis. The findings reveal that all operational service variables significantly influence transportation operational efficiency. Operational reliability emerged as the strongest determinant, followed by service responsiveness and administrative efficiency. The study also found that institutional coordination and service accessibility positively contribute to ferry transportation performance and passenger satisfaction. The novelty of this research lies in integrating public management perspectives into regional maritime transportation analysis. The findings provide practical implications for improving operational governance, administrative systems, and passenger-oriented transportation services in regional ferry transportation management.